Pengembangan E-Modul Dilengkapi Quick Response (QR) Code Pada Materi Transport dan Pertukaran Zat Pada Manusia Fase F SMA/MA - Malisa, Ossy; Susanti, Diana; Afza, Aulia (CV. ITTC INDONESIA, 2024)
. This research aims to produce biology e-module teaching materials equipped with a valid and practical Quick Response (QR) Code for SMA/MA Phase F students. The research carried out is developmental research. The model applied is a 4-D model which consists of 4 stages, namely define, design, develop, and disseminate, due to limited cost and time, research was carried out only up to the develop stage. Data was obtained directly from 5 validators. The research subjects were 2 biology teachers and 28 students in class XII Phase F of SMA Negeri 1 Pulau Punjung. Based on the validity value by strategy, media and material validators, the criteria were very valid with an average value of 92,31%. The results of practicality tests carried out by teachers and students obtained very practical criteria with an average of 95% by teachers and 91,70% by students. Based on the research that has been carried out, teaching materials in the form of e-modules have been produced on the transport and exchange of substances in humans for Phase F SMA/MA which are very valid and very practical.